Interaction between Diabetes, Stress and Cardiovascular Risk - Muhammad Abbas, Huma Naeem Tareen, Maria Shahzad, Farrukh Iqbal (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: This study investigates the relationship between stress, diabetes, and cardiovascular risk, focusing on how perceived stress affects glycemic control and cardiovascular outcomes in adults with diabetes, and how social support may buffer these effects. Methods: A cross-sectional quantitative study was conducted with 150 adult diabetic patients (Type 1 and Type 2) attending outpatient clinics in Islamabad and Rawalpindi, Pakistan, between November 2022 and April 2023. Perceived stress was measured using the Perceived Stress Scale (PSS), glycemic control using HbA1c levels, and cardiovascular risk using the Framingham Risk Score. Psychological well-being and social support were assessed with the Hospital Anxiety and Depression Scale (HADS) and the Perceived Social Support Scale (PSSS), respectively. Correlation analyses, multiple regression, and independent t-tests were used to examine the relationships between stress, glycemic control, cardiovascular risk, and social support. Results: Higher perceived stress was significantly associated with poorer glycemic control (HbA1c, r = 0.55, p < 0.01) and increased cardiovascular risk (r = 0.62, p < 0.01). Multiple regression showed stress to be a significant predictor of HbA1c (β = 0.45, p < 0.01) and cardiovascular risk (β = 0.60, p < 0.01). Participants with higher social support had better glycemic control (HbA1c 6.8 ± 1.1 vs 8.1 ± 1.4, p < 0.01), lower cardiovascular risk (18.4 ± 8.0 vs 24.2 ± 10.1, p < 0.01), and reduced anxiety and depression compared to those with lower social support. Conclusion: Perceived stress significantly worsens glycemic control and cardiovascular risk in diabetic patients, while social support acts as a protective factor. Integrating stress management and strengthening social support networks into diabetes care may improve both metabolic and cardiovascular outcomes. Keywords: Diabetes, Stress, Cardiovascular Risk, Glycemic Control, Social Support, HbA1c, Perceived Stress, Anxiety, Depression, Framingham Risk Score.